HIGH FREQUENCY SHOOTS REGENERATION FROM IN VITRO RAISED SEEDLINGS OF MURRAYA KOENIGII (L.) SPRENG. - UZMA RANI,; NAJMA ISMAIL,; GARIMA ZIBBU,; AMLA BATRA, (International Journal of Pharma and Bio Sciences, 2010)
Immature seeds of Murraya koenigii (L.) were allowed to grow in in vitro condition on ½ strength Murashige and Skoog (MS) medium. Cotyledonary node of 3-4 weeks old seedlings were taken and further cultured on Murashige and Skoog (MS) medium supplemented with BAP (5.0 mg/l) for multiple shoots with (15.85±1.0) proliferation. Shoots were separated carefully and sub-cultured to induce roots on ½ strength MS medium supplemented with IBA (1.5mg/l). Regenerated plants were successfully hardened and acclimatized with 80 % survival rate under natural conditions after transplantation.